2019
DOI: 10.1101/19007385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Quantitative and Narrative Evaluation of Goodman and Gilman’s Pharmacological Basis of Therapeutics

Abstract: Objective: Goodman and Gilmans The Pharmacological Basis of Therapeutics (GGPBT) has been a cornerstone in the education of pharmacists, physicians, and pharmacologists for decades. The objectives of this report were to describe and evaluate the 13th edition of GGPBT including 1) author characteristics; 2) recency of citations; 3) conflict of interest (CoI) disclosure, and 4) expert evaluation of chapters. Methods: Contributors (N = 115) sex, professional degrees, and presence of undisclosed potential CoI as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Researchers reviewed authors (n=31) of the online medical resource, Medscape, for potential COIs and found 19 discordant authors (61.3%) who self-reported a nothing to disclose status, but had an OP entry (12). Additionally, this investigation (12) found a strong correlation between the reported payment amounts on OP and DFD, consistent with prior research (3). A small report focused on UpToDate and DynaMed authors and editors, reviewed six articles on each site and found no COIs among DynaMed contributors and “numerous” potential COIs among UpToDate contributors (13).…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Researchers reviewed authors (n=31) of the online medical resource, Medscape, for potential COIs and found 19 discordant authors (61.3%) who self-reported a nothing to disclose status, but had an OP entry (12). Additionally, this investigation (12) found a strong correlation between the reported payment amounts on OP and DFD, consistent with prior research (3). A small report focused on UpToDate and DynaMed authors and editors, reviewed six articles on each site and found no COIs among DynaMed contributors and “numerous” potential COIs among UpToDate contributors (13).…”
Section: Introductionsupporting
confidence: 90%
“…Additionally, this investigation (12) found a strong correlation between the reported payment amounts on OP and DFD, consistent with prior research (3). A small report focused on UpToDate and DynaMed authors and editors, reviewed six articles on each site and found no COIs among DynaMed contributors and "numerous" potential COIs among UpToDate contributors (13).…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 85%
See 3 more Smart Citations